The Function Of The Land Office In Resolving Land Ownership Disputes In The Pelalawan Regency - Syaprianto, Syaprianto (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2022)
This research aims to see the function of the Land Office in resolving land ownership disputes in Pelalawan Regency, and it was carried out using qualitative research methods. Researchers interviewed direct and in-depth informants who were the most knowledgeable about implementing the Land Office's function in resolving land ownership disputes using purposive sampling techniques. The results of this study indicate that the Land Office has carried out its function in resolving land ownership disputes and is considered quite optimal because it has become a mediator for the two parties to the dispute in conducting mediation even though it has not yet reached an agreement. Several findings become obstacles for the Land Office in resolving land ownership disputes. First, the Land Office lacks human resources. Second, the lack of witnesses related to land history, and third, the character factor of the disputants who are only selfish.